High-Power Induction Motors Supplied with Voltage Containing Subharmonics - Piotr Gnaciński (Energies, 2020)
In some power networks, components of frequency less than the frequency of the fundamental voltage harmonic called subharmonics or subsynchronous interharmonics occur. In this paper, the effect of voltage subharmonics on currents, power losses, speed fluctuations and electromagnetic torque is examined. The results of numerical computations using the finite element method for an induction cage motor of rated power of 5.6 MW and four motors of rated power of 200 kW with different numbers of poles are presented. An extraordinary harmful effect on high-power induction motors is demonstrated. Among other effects, voltage subharmonics cause significant torque pulsations whose frequencies may correspond to the elastic-mode natural frequency. Possible resonance can result in excessive torsional vibration and the destruction of a power train.